Capability Development of Government Internal Control Apparatus in Improving the Effectiveness of Internal Control - Muhammad Rachmat; Chandra Wijaya (Publikasi Indonesia, 2024)
Developing the capability of the Government Internal Audit Agency (APIP) has an impact on improving performance and maintaining transparency and accountability standards. Increasing the value of the APIP Capability Model provides a comprehensive framework for analyzing and improving APIP capabilities on an ongoing basis. The purpose of this research is to analyze the factors that affect APIP capability. Analyzing the role of management in achieving the APIP capability level, analyzing the impact of APIP's role in implementing the Government Internal Control System (SPIP), analyzing the importance of APIP capacity building, analyzing the relationship between APIP capability and financial management performance, analyzing the impact of the effectiveness of implementing the Internal Audit Capability Model (IACM) in improving APIP capability. The steps suggested are practical analysis of the influence of APIP capability, including management commitment, SPIP improvement, competency improvement, focus on improving financial performance and application of IACM